MAKING PEACE AMONG CONFLICTING IDENTITIES: AN AUTOETHNOGRAPHY - Monica Ella Harendita (International Journal of Humanity Studies (IJHS), 2017)
Autoethnography has gained more popularity in qualitative research. Putting the researchers personal narratives at the centre, authoethnography can present one way to vocalize her voice without diminishing the significance of theories. By connecting lived experiences with the framework, autothnography can serve as a powerful tool in meaning makings. Drawn upon my experiences when I was pursuing my masters in Australia, this autoethnography portrays my struggle on identity negotiation as a Javanese woman and a student in Australia. As I was trying to uncover my experiences and look at them mainly using Halls (1993, 1997) theories as the framework, I came into a better understanding on my multiple and multilayered identities. Negotiating those identities is the key to make peace among them.